The intellectual capital and its valuation, as part of the intangible assets in the financial information of the company - Félix Enríquez, Sergio (Universidad de Sonora, 2017)
Currently, it has gained strength and increased its importance, currently, the value of intellectual Business, has gained; it is recognized that it must be part of the financial statements, since wealth is generated by people as well as the business itself. The problem of how to assign a value to it, is presented, so studies and business researchers have been given to the task of looking for indicators that show how people and the organizations themselves generate value by creating a series of models that are used by diverse companies especially those that are competitive and that are at the forefront in the world of business. Some models are presented in a brief way Through time they have been designing, trying to sustain the value assignment, some of them coinciding of them in the various criteria that state that They add value to companies. The current accounting regulations are analyzed, in relation to intangible assets and their treatment in regarding its valuation and reflection in the financial information The problem is how to assign value to intellectual capital in a sustained and reasonable way with the goal that from the accounting point of view is tangible and can be reflected in the financial information The work is an analytical review of the existing bibliography reaching the conclusion that There are several criteria that help to assign value to you through some manifestations and concepts that are present in individuals and in organizations but in a subjective way.